2006
DOI: 10.1111/j.1365-2869.2006.00494.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep‐disordered breathing in a general heart failure population: relationships to neurohumoral activation and subjective symptoms

Abstract: SUMMAR Y The aim of this study was to determine the prevalence of sleep-related breathing disorders (SDB) in a UK general heart failure (HF) population, and assess its impact on neurohumoral markers and symptoms of sleepiness and quality of life. Eighty-four ambulatory patients (72 male, mean (SD) age 68.6 (10) yrs) attending UK HF clinics underwent an overnight recording of respiratory impedance, SaO 2 and heart rate using a portable monitor (Nexan). Brain natriuretic peptide (BNP) and urinary catecholamines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 43 publications
5
60
0
Order By: Relevance
“…Previous reports of HF estimated a CSB prevalence of 30%-50%, a significantly lower range than in our study. 3,4 Since sleep disorder prevalence is correlated to HF severity, 5 it is conceivablethat our findings represent the true prevalence in such a cohort of patients with advanced disease. In most of the previous studies, 6 sleep apneas in HF patients were assessed by using polysomonography End-diastolic diameter (mm) 61±8 6 1 ±6 .…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Previous reports of HF estimated a CSB prevalence of 30%-50%, a significantly lower range than in our study. 3,4 Since sleep disorder prevalence is correlated to HF severity, 5 it is conceivablethat our findings represent the true prevalence in such a cohort of patients with advanced disease. In most of the previous studies, 6 sleep apneas in HF patients were assessed by using polysomonography End-diastolic diameter (mm) 61±8 6 1 ±6 .…”
Section: Discussionmentioning
confidence: 88%
“…24 This thesis is supported by other observations, in which the ''smoking gun'' of CSB in HF is repeated episodes of hypoxemia with a contribution of ventricular arrhythmia and high sympathetic tone. 5,25,26 Moreover, several studies demonstrated that even short daytime oscillatory breathing patterns are associated with poor outcome. 27,28 The main, as yet unsolved, question is whether CSB is merely a reflection of HF disease severity or whether it actually causes the clinical course of the HF disease to deteriorate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Sleep disordered breathing was considered, even though prior studies indicate that daytime sleepiness is not explained by sleep apnea in these patients. [4][5][6][7] As this variable had missing data, it was analyzed both with available data and again after multiple imputations based on age, gender and BMI at baseline. Data were imputed using the method of chained equations as implemented in the Stata program ice command.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…3 There is a growing awareness that sleep disturbances are common in HF and these symptoms are not explained by sleep disordered breathing. [4][5][6][7] Over half of HF patients report insomnia symptoms. 4 The most commonly reported problems are initiating and maintaining sleep; objective sleep assessments have shown shorter sleep duration, frequent arousals, and sleep stage changes in HF patients.…”
Section: Introductionmentioning
confidence: 99%